(untitled) (Research, Society and Development, 2022)
Introduction: The gap in the knowledge of professionals in relation to Integrative and Complementary Practices is one of the factors that make it difficult to implement these in health services, and the provision of training for changes in this scenario is relevant. Objective: To describe the perception of health professionals at a University Hospital on the use of integrative and complementary health practices. Method: Observational and descriptive study, with a quantitative approach and cross-sectional approach, developed with 109 professionals. Data collection took place between November 2020 and July 2021, through a self-administered questionnaire with questions about the characterization and perception of professionals about PICS. Results: There was a predominance of nursing professionals, between 30 and 39 years old, of mixed race, male, single, Catholic and from urban areas. There is a positive perception in relation to the practices, as the professionals agree, indicate and are interested in carrying out training, however, there is a weakness in their knowledge and familiarity with them, since many are unaware of the PNPIC or have never recommended any practice to them. patients. Conclusion: It was identified a positive perception of health professionals in relation to PICS and interest in knowing them, concomitant with little knowledge about the regulation of these practices and little professional use. Thus, it is necessary to adopt educational and permanent conducts with these professionals to promote proximity to the theme, since this is an important factor for the implementation of PICS in health services.